2020
DOI: 10.1017/thg.2020.66
|View full text |Cite
|
Sign up to set email alerts
|

Causes of Variation in Food Preference in the Netherlands

Abstract: Our current society is characterized by an increased availability of industrially processed foods with high salt, fat and sugar content. How is it that some people prefer these unhealthy foods while others prefer more healthy foods? It is suggested that both genetic and environmental factors play a role. The aim of this study was to (1) identify food preference clusters in the largest twin-family study into food preference to date and (2) determine the relative contribution of genetic and environmental factors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 34 publications
(62 reference statements)
4
15
0
Order By: Relevance
“…We found that variations in overall diet quality measured by diet scores are heritable, with estimates varying between 42% (A-HEI) and 5% (HDI). These estimates are comparable with the results reported in previous studies investigating the heritability of food preference in adults (Pallister et al, 2015;Smith et al, 2016;Törnwall et al, 2014;Vink et al, 2020). In this study, the interclass correlations were always higher in MZ pairs than in DZ pairs (which suggested a strong genetic component).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…We found that variations in overall diet quality measured by diet scores are heritable, with estimates varying between 42% (A-HEI) and 5% (HDI). These estimates are comparable with the results reported in previous studies investigating the heritability of food preference in adults (Pallister et al, 2015;Smith et al, 2016;Törnwall et al, 2014;Vink et al, 2020). In this study, the interclass correlations were always higher in MZ pairs than in DZ pairs (which suggested a strong genetic component).…”
Section: Discussionsupporting
confidence: 91%
“…None of the studies found evidence of the effects of common environmental component (C) (Pallister et al, 2015;Smith et al, 2016). A dominant genetic effect (D) was only identified for some food preferences (fruit and fish in females; Smith et al, 2016;Vink et al, 2020), but for most of the food preferences, the dominant genetic component was not detected (Smith et al, 2016;Vink et al, 2020). These results are in line with our findings.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Food-liking traits were collected through an online questionnaire comprising 152 items, including both foods and non-food items, which was administered in 2019 to all UK Biobank participants who had agreed to be recontacted by the study. The questionnaire is an extension of the one previously used in Pallister et al 2015 13 and Vink et al 2020 15 . Given that the questionnaire was administered online to participants pictures were removed, and we used a 9-point Hedonic scale 27 , where corresponds to "Extremely dislike" and 9 to "Extremely like".…”
Section: Food-liking Phenotypesmentioning
confidence: 99%